The Thriving Adolescent : Using Acceptance and Commitment Therapy and Positive Psychology to Help Teens Manage Emotions, Achieve Goals, and Build Connection. - Hayes, Louise L. (New Harbinger Publications, 2015)
The Thriving Adolescent offers teachers, counselors, and mental health professionals powerful techniques for working with adolescents. Based in proven-effective acceptance and commitment therapy (ACT), the skills and tips outlined in this book will help adolescents and teens manage difficult emotions, connect with their values, achieve mindfulness and vitality, and develop positive relationships with friends and family. This is the first book to apply ACT to treating this population.